Intelligence and Delinquency - Shulman, Harry (1951)
The study of the relationship of intelligence and delinquency began with the early 19th century neo-classical criminal justice doctrine that since crime was a rational choice of conduct, mental defectives in common with infants and the insane, were not legally responsible for their actions. While the medical differentiation of mental defectives from the insane was accomplished during the early part of the 19th century, it was not until the late 19th century that scientific standards were established for the measurement of degrees of mental ability and for the determination of mental defect, despite man's observation since time immemorial of the individual variability in mental ability. These were tests for general intelligence, the product of research by a whole school of psychologists, but attributable directly to the researches of Alfred Binet, of France